Nilai Ekonomi Dan Kontribusi Hasil Hutan Bukan Kayu Terhadap Pendapatan Masyarakat Desa Bakubakulu Kecamatan Palolo Kabupaten Sigi - Sugara, Bayu; Umar, Syukur; Golar, Golar (Universitas Tadulako, 2022)
This research aims: to determine the economic value and contribution of NTFPs to community income and the level of sustainability of NTFPs. NTFP Management in Bakubakulu Village. The type of research is quantitative descriptive, with a total of 40 families as informants. The research results show that NTFPs have high economic value. The highest economic value is owned by the candlenut type, amounting to Rp. 14,688,000/year, palm sugar Rp. 10,080,000/year and palm sap Rp. 10,392,000/year. The business feasibility of candlenut, palm sugar and sap products in Bakubakulu Village has an R/C value of more than 1, meaning that the total income is still greater than the total production costs and business activities for utilizing NTFP products. still feel the benefits. The contribution of HHBK utilization to the income of the Bakubakulu Village community is 44.61% or around Rp. 35,160,000/year. In order for the community to obtain the maximum economic benefits while providing environmental services, it is necessary to increase technical, institutional and educational capacity in managing NTFPs.